PENERAPAN REALISTIC MATHEMATICS EDUCATION PADA PEMBELAJARAN MATEMATIKA SISWA BERKESULITAN MEMBACA - Endah Farida Ariyani; Anggita Maharani (LPPM Universitas Bina Bangsa, 2023)
In learning activities at school we often find students who have learning difficulties, including students who have difficulty reading. Reading difficulties in learning mathematics will have an impact on students' understanding of mathematical concepts, one of the efforts that can be made to overcome these problems is to apply the Realistic Mathematics Education (RME) approach. This study aims to determine the application of the Realistic Mathematics Education (RME) approach to learning mathematics for students with reading difficulties. The method used in this research is Single Subject Research (SSR) A-B design with the first condition Baseline (A) and the second condition B (Intervention). The results showed that the application of RME improved the understanding of mathematical concepts of students with reading difficulties in comparison materials